Consumer Protection Against Fraudulent Practices by Online Motorcycle Taxi Drivers in Medan City - Vira Nur Fadillah Lubis; Fatimah Zahara (Hakamain: Journal of Sharia and Law Studies, 2025)
The rapid growth of online motorcycle taxi services in Indonesia has significantly transformed urban transportation systems, including in Medan City. Alongside this development, various fraudulent practices by online motorcycle taxi drivers have emerged, such as fare manipulation, fictitious orders, service cancellations after payment, and deviations from agreed routes, which potentially harm consumers. This study examines consumer protection against fraudulent practices by online motorcycle taxi drivers in Medan City, focusing on the adequacy and effectiveness of the existing legal framework. This research employs a normative juridical method supported by a socio-legal and empirical field research approach. Primary legal materials include Law Number 8 of 1999 on Consumer Protection, transportation regulations, and platform-based service policies, while secondary materials consist of scholarly articles and legal commentaries on consumer protection in digital transportation services. Field research was conducted through interviews with consumers, online motorcycle taxi drivers, and local transportation officials in Medan City, as well as analysis of reported consumer complaints. The findings indicate that although Indonesian consumer protection law formally guarantees consumers’ rights to safety, accurate information, and fair treatment, its implementation in online motorcycle taxi services remains inadequate. Weak regulatory supervision, limited consumer awareness, and unclear responsibility-sharing between drivers and platform providers contribute to ineffective legal protection. This study contributes to legal scholarship by identifying regulatory gaps and enforcement challenges in platform-based transportation services and recommends strengthening regulatory oversight, enhancing platform accountability, and improving consumer education to ensure effective consumer protection and sustainable development of online transportation services in Medan City.